Recycling of Low-Value Hydrocarbon Cuts by Means of Multiple Injections to FCC Units - Tiscornia, Ines Silvia (2002)
The upgrading of a visbreaker naphtha by recycling it into an FCC unit was studied following the approach of multiple injections (with the naphtha in the first one) using a laboratory riser simulator reactor and an equilibrated catalyst. The experimental work comprised three different stages:  a study of the crackability of the naphtha under conventional FCC conditions (500−550 °C, CATOIL 6.1, short contact times), a study of the conversion of the naphtha under a regime of high severity (CATOIL 37), and a study of the impact of this injection on the overall FCC operation. Heavy C7−C9 olefins and n-paraffins are converted, and aromatics and C4−C6 i-paraffins are the most noticeable products. Even though the RON in the gasoline cut of the products does not change, modifications in the composition are advantageous because heavy olefins and n-paraffins are selectively converted. The high-severity regime induces more profound changes in the composition of the gasoline cut that significantly improve the blending properties. More importantly, the first injection would not interfere with the standard feedstock injection, because catalyst properties and performance are not altered, as shown by experiments with coked and regenerated catalyst.